(untitled) (Research, Society and Development, 2020)
The aim of this study was to analyze pre-competitive anxiety based on the age range and competitive classification of 26 jiu-jitsu athletes aged 25.5 ± 5.24 years. The instrument used was the Competitive State Anxiety Inventory-2 (CSAI-2). Data analysis was conducted using the Shapiro-Wilk, independent Student’s t-test, Pearson’s correlation and simple linear regression (p <0.05). The results revealed that older and more competitive athletes presented a lower magnitude of cognitive anxiety (p <0.05). We observed a moderate and inverse association (r = -0.63, p <0.05) between cognitive anxiety and age, accounting for 38% (R2 = 0.38) of the variance of cognitive anxiety in athletes. It was concluded that age and competitive classification can be considered as intervening factors in the pre-competitive anxiety of jiu-jitsu athletes, specifically in cognitive anxiety.